Exploring Mental Accounting Behavior towards Debt To Income Ratio of Shopee Paylater Feature Users - Lestari, Dianita; Mulawarman, Aji Dedi (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This phenomenological study aims to explore the impact of mental accounting behavior on the debt-to-income (DTI) ratio among Shopee PayLater users. The data were collected through interviews with four undergraduate students of Universitas Brawijaya. The analysis revealed that while students understood the concept of mental accounting in managing their Shopee PayLater payments, they tended to apply it with overconfidence, leading to counterproductive financial decision-making. This was reflected in their DTI ratios, which ranged from 41% to 74%, indicating a high risk of default resulting from inconsistencies in financial management, especially in the management of debt usage.